Prevention of kainic acid-induced changes in nitric oxide level and neuronal cell damage in the rat hippocampus by manganese complexes of curcumin and diacetylcurcumin - Yaowared Sumanont (2018)
Curcumin is a natural antioxidant isolated from the medicinal plant Curcuma longa Linn. We previously reported that manganese complexes of curcumin (Cp-Mn) and diacetylcurcumin (DiAc-Cp-Mn) exhibited potent superoxide dismutase (SOD)-like activity in an in vitro assay. Nitric oxide (NO) is a free radial playing a multifaceted role in the brain and its excessive production is known to induce neurotoxicity. Here, we examined the in vivo effect of Cp-Mn and DiAc-Cp-Mn on NO levels enhanced by kainic acid (KA) and l-arginine (l-Arg) in the hippocampi of awake rats using a microdialysis technique. Injection of KA (10 mg/kg, i.p.) and l-Arg (1000 mg/kg, i.p.) significantly increased the concentration of NO and Cp-Mn and DiAc-Cp-Mn (50 mg/kg, i.p.) significantly reversed the effects of KA and l-Arg without affecting the basal NO concentration. Following KA-induced seizures, severe neuronal cell damage was observed in the CA1 and CA3 subfields of hippocampal 3 days after KA administration. Pretreatment with Cp-Mn and DiAc-Cp-Mn (50 mg/kg, i.p.) significantly attenuated KA-induced neuronal cell death in both CA1 and CA3 regions of rat hippocampus compared with vehicle control, and Cp-Mn and DiAc-Cp-Mn showed more potent neuroprotective effect than their parent compounds, curcumin and diacetylcurcumin. These results suggest that Cp-Mn and DiAc-Cp-Mn protect against KA-induced neuronal cell death by suppression of KA-induced increase in NO levels probably by their NO scavenging activity and antioxidative activity. Cp-Mn and DiAc-Cp-Mn have an advantage to be neuroprotective agents in the treatment of acute brain pathologies associated with NO-induced neurotoxicity and oxidative stress-induced neuronal damage such as epilepsy, stroke and traumatic brain injury. © 2005 Elsevier Inc. All rights reserved.